DNA Damage Repair Gene Mutations Are Indicative of a Favorable Prognosis in Colorectal Cancer Treated With Immune Checkpoint Inhibitors - Song, Yipeng; Huang, Jian; Liang, Dandan; Hu, Ying; Mao, Beibei; Li, Qiujing; Sun, Huaibo; Yang, Ying; Zhang, Jiao; Zhang, Henghui; Chen, Huan; Liu, Hao; et al. (Frontiers in Oncology, 2021)
Abstract Background: DNA damage response (DDR) genes were recently implicated in the anti-tumor immune response. Therefore, it is worthwhile to unravel the implications of DDR pathways in the shaping of immune responsiveness in colorectal cancer (CRC) patients receiving immune checkpoint inhibitors (ICI). Methods: We analyzed publicly available genomic data from a cohort treated with ICI from Memorial Sloan Kettering Cancer Center (MSK ICI cohort). To characterize the impact of the DDR mutation, the genomic data of The Cancer Genome Atlas (TCGA) colorectal adenocarcinoma (COADREAD) dataset was explored. We also analyzed the incidence of DDR mutation and microsatellite instability-high (MSI-H) in a Chinese CRC cohort using panel sequencing. Results: The DDR pathway was commonly mutated (21.8%) in the multicancer MSK ICI cohort, with the highest frequency of 36.4% in CRCs. Survival analysis showed that DDR mutation correlated with an improved overall survival (OS) in CRCs and pan-cancer in the MSK ICI cohort. However, no significant associations were identified in the TCGA COADREAD and MSK non-ICI CRCs. DDR mutation was associated with higher tumor mutational burden (TMB) levels and increased immune cell infiltration and immune checkpoint molecule expression in the TCGA COADREAD dataset. Last, we investigated the DDR mutational pattern and its associations with MSI-H and other genomic features in a Chinese CRC cohort. Notably, MSI-H and DDR mutation was present in 5.7% and 13.4% of cases, respectively, which suggests that DDR identifies a higher proportion of potential responders than MSI-H. Conclusion: Our data suggest that DDR mutation as an indication of enhanced cancer immunity, and it may function as a biomarker for patients with CRCs receiving ICI treatment. The high incidence of DDR mutation in the Chinese CRC cohort emphasizes the future utility of panel-based DDR evaluation in guiding ICI treatment.